Analisis Percepatan Aktifitas Pada Proyek Jalan Dengan Menggunakan Metode Fast Track , Crash Program, Dan What-If - Andrea Saputra A. P.; As’ad Munawir; Indradi Wijatmiko (Rekayasa Sipil, 2017)
Implementation of road projects southern cross wawar - congot purworejo central java at week 27 is delayed. From 53.41% is only realized 12.82%. Fast track method, the program crashes, and what if is used to accelerate the implementation of delayed project. The purpose of this study is to determine the acceleration of implementation, to evaluate the effectiveness acceleration and to evaluate the implementation of road projects based on the control of time and cost. Time control and costs control shows sv 0.24 and cv value of 1.06, and it explains that the project is delayed, but the cost is less from the plan. Fast track method can accelerate 78 days, crash program method can accelerate 31 days, and what if method can accelerate to 7 days from prior to the acceleration, which is 110 days late. All three methods cannot speed up the project based on the plan. Fast track method is the method most quickly approaching the initial plan. Then combination of acceleration between fast track and a crash program produce total duration as scheduled. The conclusion is the combination of methods can restore the schedule according to the plan.